Progression of psychological readiness to return to sport and the influence of Covid-19 on rehabilitation after anterior cruciate ligament reconstruction - Zelleroth, Y. (University Örebro, 2021)
Introduction: A successful return to sport (RTS) after anterior cruciate ligament reconstruction (ACL-R) demands optimal physical and psychological rehabilitation.